Effect of supplement levels on creep-feeding for suckling calves and prepartum Nellore cows on pasture - Saraiva, Douglas Teixeira (2023)
In the first experiment, the study aimed to evaluate the effects of different levels of supplementation on the nutritional and productivity performance and metabolic parameters in beef calves fed in tropical grass pastures and the costs of this supplementation. Thirty-five Nellore male calves, with an average body weight (BW) of 115 ± 12 kg and an average age of 110 ± 10 days, and their dams (BW = 505 ± 25 kg, 8 years of age) were used. The supplementation levels were as follows: 0 = in the control group, calves received only a mineral mixture; one group received 5 g/kg BW of supplementation with 250 g of crude protein/kg of dry matter; and another group received 10 g/kg BW with 250 g of crude protein/kg of dry matter. The experimental design was completely randomized. The cow-calf pairs were randomly assigned to an experimental area of eight plots, and a group of four to five animals was considered one experimental unit. The intakes of dry matter (DM), organic matter (OM), crude protein (CP), and total digestible nutrients (TDN) (P<0.05) were greater for calves that received a higher level of supplementation. However, supplementation did not affect the milk production and productive performance of the cows (P>0.05). Supplementation increased the apparent digestibility of DM, OM, CP, and non-fiber carbohydrates (NFC), with digestibility increasing as inclusion of the supplement increased (P<0.05). The calves receiving 10 g/kg BW supplementation showed a higher average daily gain (ADG) and thus a higher weight at weaning (P<0.05) and higher concentrations of blood urea nitrogen (BUN) and insulin-like growth factor 1 (IGF-1). However, considering the good quality of the forage offered during the study period, an improvement in performance and nutritional characteristics was observed for the 10 g/kg BW treatment, however, without economic gain in the non-supplemented animals. In the second experiment, the objective was evaluate the effects of different supplementation strategies for Nellore cows 60 days prepartum on performance, metabolic responses and influence on the initial body development of the offspring. We used 39 pluriparous, gestating male Nellore cows with an initial mean of 224 ± 2.6 days of pregnacy, 520 ± 15.2 kg body weight (BW) and 6.0 ± 0.07 (scale of 1 - 9) body condition score (BCS), according to completely randomized design, with four treatments and two repetitions. The treatments evaluated were: control receiving only mineral mixture ad libitum, 2 g/kg BW, 4 g/kg BW and 6 g/kg BW of protein-energy supplement per cow per day for 60 days before calving. The supplement was formulated to contain similar amounts of crude protein, 300 g BW/kg in DM. Statistical evaluations were conducted using the PROC MIXED procedure of SAS (version 9.4), adopting α = 0.05. Cows supplemented with 4 and 6 g/kg BW showed greater BW variation in the prepartum and less variation in the postpartum (P<0.05). There was a higher BCS for supplemented animals (P<0.05) at calving and at 90 days postpartum, with animals in the 4 and 6 g/kg BW treatment being higher than the control treatment (P<0.05). There were no differences in calf birth weight and performance up to 90 days postpartum (P>0.05). Animals receiving 4 and 6 g/kg BW had a shorter service period compared to the control treatment (P<0.05), but there were no differences for overall pregnancy outcome (P>0.05). Treatment x day interaction was observed for BUN which was higher in the prepartum for animals that received higher supplementation levels (P<0.05), βHB, was higher in the prepartum for animals in the control treatment (P<0.05), and for NEFA, concentrations were lower 21 days before calving and at 21 and 42 days after calving, for the treatments that received 4 and 6 g/kg BW (P<0.05). Progesterone concentrations presented a positive linear effect with the increase of supplement supply (P<0.05), being higher for animals that received 4 and 6 g/kg BW compared to animals in the control treatment (P<0.05). In view of these results, Providing 4g/kg BW of protein-energy supplement to grazing Nellore cows 60 days prior to calving is recommended, which improves metabolic characteristics and performance in the prepar-tum and postpartum period and a lower negative energy balance in the postpartum period, resulting in a shorter service period. Keywords: Creep-feeding. Cows. Nutrition. Physiology. NEFA. Progesterone.